International entrepreneurship in Japan: an extended model. (6th July 2010) - Gaspari, Paul; Haghirian, Parissa
The study of international entrepreneurship is a growing one in the academic field. However, studies have been limited and scarce in analysing the role of expatriates in starting businesses overseas. Using Japan as a case study, the authors propose a model consisting of 14 variables that can be tested to show the rate of success or failure for a foreign entrepreneur in another country.